Prediction of venous thromboembolism in patients with multiple myeloma treated with lenalidomide, bortezomib, dexamethasone, and transplantation: Lessons from the substudy of IFM/DFCI 2009 cohort. (24th May 2022) - Chalayer, Emilie; Talbot, Alexis; Frenzel, Laurent; Karlin, Lionel; Collet, Philippe; Guyotat, Denis; Attal, Michel; Leleu, Xavier; Tardy, Bernard
Abstract: Background: Venous thromboembolism (VTE) is a concern for patients with newly diagnosed multiple myeloma. Objectives: We aimed to evaluate VTE incidence, risk factors, and risk score. Patients/Methods: We performed a substudy of the "Intergroupe Francophone du Myelome 2009" randomized controlled trial. Results: We assessed 700 patients receiving lenalidomide/bortezomib/dexamethasone, followed or not by autologous hematopoietic stem cell transplantation. VTE incidence at 6 months was 4.8% (95% confidence interval [CI]: 3.3–6.9%) and 1.5% (95% CI: 0.8–2.9%) from 6 to 12 months. Using multivariate analysis we confirmed history of VTE (odds ratio 5.1 [1.6–16.7], P = .007) as a strong VTE‐related risk factor, invalidated erythropoietin exposure (0.6 [0.2–1.7], P = .3) as risk factor, and added two new risk factors: fracture at diagnosis (2.6 [1.3–5.5], P = .01), and serum gamma globulin level > 27 g/L (2.8 [1.2–6.8, ] P = .02). Moreover, we noticed that VTE occurred earlier in patients with gamma globulin levels >27 g/L, suggesting a need to revisit the thromboprophylaxis timeframe. Heparin administration was associated with a decreased risk (0.3 [0.1–0.7], P = .005) but failed to erase the risk regardless of dose. The area under the receiver operating characteristic curve of the IMPEDE VTE score was 0.67, as previously reported, confirming our cohort was well representative. Conclusions: Prospective studies are warranted in light of these results to improve VTE risk stratification and to design adapted thromboprophylaxis in terms of timing and dose.